Sociocultural, health knowledge, and health literacy among children ages 9-10 years in Thailand - Nopparat Senahad; Wongsa Loahasiriwong; Naowarat Maneenin (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Health literacy (HL) enables a person to make good decisions regarding health care, disease prevention, and health promotion to maintain and improve health. In Thailand, most existing studies focus on adults' HL rather than children. This research aimed to determine the influence of sociocultural and health knowledge on HL among children ages 9-10 years in Thailand. MATERIALS AND METHODS: A cross-sectional study was conducted among 1650 children aged 9-10 years. The respondents were recruited using multistage random sampling from 39 primary schools of 13 provinces in all four regions of Thailand. A self-administered structured questionnaire was used to collect the required data. The multilevel analysis was used to determine the association between sociocultural, health knowledge, and HL while controlling the effects of covariates. The result was presented as adjusted odd ratios and its 95% confidence interval (CI). RESULTS: Of the total 1650 respondents, 86.24% (95% CI: 84.49%-87.82%) had adequate and excellent levels of HL. The multivariable analysis indicated factors that were significantly associated with adequate and excellent levels HL including adequacy of per diem (adjusted odds ratio [adj. OR] = 6.78; 95% CI: 3.54-12.97) and had good relationship with teachers (adj. OR = 2.19; 95% CI: 1.55-3.09). Sources of health education which were received health education from parents (adj. OR = 3.51; 95% CI: 2.39-5.14), from teachers (adj. OR = 2.03; 95% CI: 1.43-2.89), and from the Internet (adj. OR = 1.83; 95% CI: 1.12-2.99) were also significantly associated with HL. Another significant factor was had good level of health knowledge (adj. OR = 1.86; 95% CI: 1.30-2.66) when control clustering effect of region, provinces, school, and classroom size. CONCLUSIONS: More than 85% of children ages 9-10 years in Thailand had adequate and excellence levels of HL. Sociocultural and health knowledge had influence on children HL.